`y = cos(x)/(1 - sin(x))` Differentiate.

Textbook Question

Chapter 3, 3.3 - Problem 12 - Calculus: Early Transcendentals (7th Edition, James Stewart).
See all solutions for this textbook.

1 Answer | Add Yours

goodthink's profile pic

goodthink | Student, Grade 12 | (Level 1) Honors

Posted on

Quotient Rule:

`y'=(((-sin(x))*(1-sin(x))-(-cos(x))(cos(x)))/((1-sin(x))^(2))) `

`y'=(((cos^(2)(x))+(sin(x))*(sin(x)-1))/((sin(x)-1)^(2)))`

This can simplify to 

`y' = 1/(1 - sin(x))`

We’ve answered 318,960 questions. We can answer yours, too.

Ask a question